2021
DOI: 10.1103/physrevapplied.16.024043
|View full text |Cite
|
Sign up to set email alerts
|

Photoporomechanics: An Experimental Method to Visualize the Effective Stress Field in Fluid-Filled Granular Media

Abstract: Effective stress governs the mechanical behavior of porous media. In this study, we use photoelasticimetry to visualize the evolving effective stress field in fluid-filled granular media in processes that couple fluid flow and mechanical deformation. We refer to this experimental method as photoporomechanics. We develop a fabrication process to produce millimeter-scale residual-stress-free photoelastic spheres with high geometric accuracy. We use color to quantify the forces acting on the particles over a wide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 57 publications
0
9
0
Order By: Relevance
“…In summary, we have studied the morphology and rheology of injection-induced fracturing in cohesive wet granular packs via a recently developed experimental technique, photoporomechanics, which extends photoelasticity to granular systems with a fluid-filled connected pore space. 32 Experiments of water injection into cohesive photoelastic granular packs with different tensile strength, injection flow rate, and defending fluid viscosity have led us to uncover two invasion regimes: viscous fingering, and fracturing with leak-off of the injection fluid. Contrary to the observed effective stress shadow for cohesionless granular packs, 31 here we discover a hoop effective stress region behind the water invasion front.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In summary, we have studied the morphology and rheology of injection-induced fracturing in cohesive wet granular packs via a recently developed experimental technique, photoporomechanics, which extends photoelasticity to granular systems with a fluid-filled connected pore space. 32 Experiments of water injection into cohesive photoelastic granular packs with different tensile strength, injection flow rate, and defending fluid viscosity have led us to uncover two invasion regimes: viscous fingering, and fracturing with leak-off of the injection fluid. Contrary to the observed effective stress shadow for cohesionless granular packs, 31 here we discover a hoop effective stress region behind the water invasion front.…”
Section: Discussionmentioning
confidence: 99%
“…The photoelastic response offers a unique opportunity to gain additional understanding of the coupled pore-scale flow and particle mechanics during fluid-induced fracturing of the cohesive granular pack. To interpret the photoelastic response, we rely on the results of calibration experiments, 32 which have shown that, for the range of interparticle forces expected in our fracturing experiments, the relation between light intensity and force is monotonically increasing and approximately linear.…”
Section: Effective Stressmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, quantitative studies [6,7] have largely focused on 2D particle systems, primarily flat discs [8], but also non-spherical shapes such as ellipses [9] and pentagons [10]. While experiments on monolayers of photoelastic spheres can be found in the literature [11][12][13], interpretations of the resulting fringe patterns remains challenging, even when the system is index-matched. In response to these experimental limitations, there have been advances in computational modelling by using the Finite Element Analysis (FEA) method.…”
Section: Introductionmentioning
confidence: 99%
“…To date, quantitative studies [6,7] have largely focused on 2D particle systems, primarily flat discs [8], but also non-spherical shapes such as ellipses [9] and pentagons [10]. While there have been recent experiments on monolayers of photoelastic spheres [11][12][13], it remains a challenge to interpret the resulting fringe patterns, even when the system is index-matched.…”
Section: Introductionmentioning
confidence: 99%